2020
DOI: 10.3390/biomedicines8090334
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Ras-Associated Protein 1 (Rap1) in Cancer: Bad Actor or Good Player?

Abstract: Metastasis is known as the most life-threatening event in cancer patients. In principle, the immune system can prevent tumor development. However, dysfunctional T cells may fail to eliminate the tumor cells effectively and provide additional survival advantages for tumor proliferation and metastasis. Constitutive activation of Ras-associated protein1 (Rap1) has not only led to T cell anergy, but also inhibited autophagy and supported cancer progression through various oncogenic events. Inhibition of Rap1 activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 120 publications
0
41
0
Order By: Relevance
“…On the other hand, Src triggered by Rap1 signaling may activate the MAPK/ERK pathway, which has been found in some research to promote G0/G1 to S phase cell cycle progression and angiogenesis in cancer 62 65 . Thus, these FImRNAs' function and signaling pathways are associated with the occurrence and development of tumors.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Src triggered by Rap1 signaling may activate the MAPK/ERK pathway, which has been found in some research to promote G0/G1 to S phase cell cycle progression and angiogenesis in cancer 62 65 . Thus, these FImRNAs' function and signaling pathways are associated with the occurrence and development of tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in the prostate cancer [ 18 ], glioblastoma [ 19 ], non-small-cell lung cancer [ 20 ], melanoma [ 21 ], breast cancer [ 22 ], and pancreatic cancer [ 23 ], RAP1 revealed a prooncogenic activity to promote invasion and migration of tumor cells. On the other hand, GTPase activating protein RAP1GAP acts as a negative regulator of Rap1 activity, which is always found to be downregulated in many cancers [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…RAS-associated protein 1 (RAP1), a member of the small G protein family of RAS, influences the tumor development and progression by engaging in various biological processes such as cell proliferation, invasion, migration, and apoptosis imbalance [ 42 , 43 ]. A recent study showed that PP2Ac nitration during cAMP-induced decidualization of hESCs was induced through the Epac1-Rap1-PLC ε -CaMKII-HDAC5-iNOS signaling pathway [ 44 ].…”
Section: Discussionmentioning
confidence: 99%